Conservation of wetland habitats and their biodiversity: an integrated approach to combat adverse impacts of global warming on them - Ansari, Abdul Haseeb (s.n, 2012)
Wetlands, natural and man-made, have close nexus with the phenomenon of global warming which is resulting in unusual weather conditions. The rise of average global temperature and related unusual weather condition, e.g. cyclones, tornado's and famines are adversely affecting wetlands around the world